Coda al commiato - Alberto Peruzzi (Firenze University Press, 2012)
The present paper collects some entries excluded from the original 1998 pamphlet titled "commiato dal Commiato" (a small farewell to the Great Farewell to "modernity" in philosophy), thus it tackles often with sarcastic flavour topics such as relativism, hermeneutics, fragmented knowledge, which mainly concern the debate between analytic and continental philosophy. The entries are related to each other in a sort of hypertextual structure rather than in a linear order.